Calcifying fibrous tumour: a rare case report of an exceptional lesion localized in retroperitoneum, mesentery and pelvis - Hathila, R. N.; Shah, Pinal C.; Patel, Archana V.; Sheth, Sheetal P. (International Journal of Research in Medical Sciences, 2020)
Calcifying fibrous tumours are rare benign lesions affecting mostly children and young adults. A 17-year-old female presented with abdominal pain and abdominal distention. Physical examination revealed intra-abdominal mass occupying retro peritoneum and right iliac fossa. Excisional biopsy from peritoneum and mesentery were performed. Histopathologically, it was composed of hypocellular hyalinised collagenized stroma, spindle cells, psammomatous and dystrophic calcification and mononuclear inflammatory cell infiltration. Authors are here in reporting a case of calcifying fibrous tumour and discussing its clinical and morphological features with regard to the literature.